M2 macrophage-based classification identifies DOK3 as a driver of pro-tumoral polarization and migration in glioblastoma - Ren, Chang-Yuan; Shi, Ji; Yang, Chang-Lin; Zhang, Jin-Hao; Tan, Wen-Lu; Zhou, Han-Xiao; Ren, Pan-Yu; Cvitković, Josip; Fan, Wen-Hua; Zhang, Ying; Zhao, Zheng (Frontiers in Immunology, 2026)
BackgroundGlioblastoma (GBM) is the most aggressive primary brain tumor, characterized by limited therapeutic options and dismal prognosis. Among the components of the immunosuppressive tumor microenvironment (TME), M2-polarized macrophages are pivotal mediators of tumor progression, yet the molecular mechanisms underlying their polarization and pro-tumoral functions remain inadequately understood.MethodsWe integrated bulk and single-cell RNA sequencing datasets from CGGA, TCGA, and GSE131928. M2 macrophage infiltration was quantified using the xCell algorithm, and unsupervised clustering of M2-associated genes was first performed to define macrophage-centered immune subtypes, further refined by XGBoost and LASSO modeling. Based on the molecular features of the most immunosuppressive subtype, a macrophage-associated risk score based on CTSB, LITAF, and DOK3 was constructed and validated across independent cohorts for prognostic and immune relevance. Functional validation was performed by silencing DOK3 in THP-1–derived macrophages, followed by co-culture with glioma cells to assess macrophage polarization and tumor cell behavior.ResultsElevated M2 macrophage infiltration correlated with reduced tumor purity, spatial heterogeneity, and worse survival. Three immune subtypes (C1–C3) were identified; notably, the C1 subtype exhibited the highest M2 infiltration, strongest immunosuppressive features, and poorest prognosis. The derived macrophage-based risk score robustly stratified patient survival and correlated with CD163 expression and immune checkpoint activation. Single-cell analysis revealed predominant DOK3 expression in macrophages and microglia. Functional assays demonstrated that DOK3 knockdown reduced CD163 expression and attenuated glioma cell invasiveness, supporting its role in promoting M2 polarization and tumor aggressiveness.ConclusionThis integrative analysis identifies DOK3 as a pivotal regulator of M2 macrophage polarization and a driver of glioblastoma progression. Together, immune subtyping and the simplified macrophage-based risk model represent complementary strategies, with the latter providing a practical tool for prognostic stratification. Targeting DOK3 offers a promising therapeutic strategy to reprogram the TME and improve clinical outcomes in patients with GBM.